Green practices and sustainability as precursors to the intention to participate again in sporting events held in nature - Chaves-Castro, Karla; Morán-Gámez, Guillermo; Nuviala, Alberto; Fernández-Martínez, Antonio (Frontiers in Sports and Active Living, 2025)
IntroductionIn recent years, the need to tackle major environmental challenges has increased awareness among organisations seeking to promote sustainable practices and minimise the impact of their events. This is a challenge for sports organisations and promoters, as they must offer high-quality events that meet the needs of the participants and, at the same time, are environmentally friendly.ObjectiveTo explore the relationship between sustainability, green practices, quality, satisfaction and intentions to participate again in sports events held in nature in Costa Rica. Methodology: 781 participants (66.3% men and 33.7% women), with an average age of 40.9 ± 11.9 years. We used a questionnaire composed of 24 items taken from different validated scales. For the purpose of data analysis, we applied various statistical techniques, including the calculation of descriptive statistics, Cronbach's alpha index, the average variance extracted, composite reliability and structural equation models.ResultsSustainability is an important determining factor of event quality. We also found that green practices positively influence event quality. In addition, the emotions experienced by the participants have a significant impact on event quality, as well as on their intentions to participate again in the future.ConclusionsThe implementation of green and sustainable practices is fundamental in the management of sporting events held in natural spaces, since they not only contribute to reducing environmental impact, but can also improve the quality of the event. In turn, these variables, along with the positive emotions experienced during the event, influence the participants' intentions to participate again on future occasions.